2021
DOI: 10.3389/fmars.2021.723998
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Variate Analyses of Coral Mortality From the 2014–2015 Stony Coral Tissue Loss Disease Outbreak Off Miami-Dade County, Florida

Abstract: Environmental compliance monitoring associated with the Port Miami dredging project (2013–2015), designed to assess the impact of project-generated sediments on the local coral community, fortuitously captured a thermal bleaching event and the first reports of an emergent, highly contagious, white-plague-like coral disease outbreak in the fall of 2014. The disease, now termed stony coral tissue loss disease (SCTLD), has decimated reefs throughout Florida and is now spreading across the Caribbean. The high prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 98 publications
0
8
0
Order By: Relevance
“…First observed in 2014 off Virginia Key in Miami-Dade County, Florida, stony coral tissue loss disease (SCTLD) has become perhaps the most damaging described coral disease to date (Walton et al, 2018;Gintert et al, 2019;Spadafore et al, 2021). Since then, it has spread throughout the entirety of Florida's Coral Reef, notably reaching the Dry Tortugas in 2021 (NOAA, 2018;Dobbelaere et al, 2020b;Muller et al, 2020;Roth et al, 2020;Sharp et al, 2020), and has now been observed in a growing number of Caribbean territories (Alvarez-Filip et al, 2019;Meiling et al, 2020;Roth et al, 2020;Dahlgren et al, 2021;Estrada-Saldívar et al, 2021;Heres et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First observed in 2014 off Virginia Key in Miami-Dade County, Florida, stony coral tissue loss disease (SCTLD) has become perhaps the most damaging described coral disease to date (Walton et al, 2018;Gintert et al, 2019;Spadafore et al, 2021). Since then, it has spread throughout the entirety of Florida's Coral Reef, notably reaching the Dry Tortugas in 2021 (NOAA, 2018;Dobbelaere et al, 2020b;Muller et al, 2020;Roth et al, 2020;Sharp et al, 2020), and has now been observed in a growing number of Caribbean territories (Alvarez-Filip et al, 2019;Meiling et al, 2020;Roth et al, 2020;Dahlgren et al, 2021;Estrada-Saldívar et al, 2021;Heres et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Dredging operations in southeast Florida, such as the Port of Miami expansion that occurred in 2013-2015, can cause the release of sediments onto local coral reef habitats (Walker et al, 2012;Miller et al, 2016;Cunning et al, 2019), which can lead to smothering of colonies in extreme cases, as well as sedimentation-associated stress and mortality (Vargas-Ángel et al, 2006(Vargas-Ángel et al, , 2007Erftemeijer et al, 2012;Shore-Maggio et al, 2018). While it is difficult to disentangle coral mortality due to sedimentation, SCTLD, or a prior thermal stress event, several studies suggest that sedimentation played a role in sublethal and lethal effects on local coral populations due to the dredging of Port of Miami (Miller et al, 2016;Cunning et al, 2019;Gintert et al, 2019;Spadafore et al, 2021). Additionally, the plume was observed through remote sensing platforms over an estimated 228 km 2 in southeast Florida (Barnes et al, 2015), suggesting the potential for spread of the pathogen(s) through local currents and sediment transport to northward reefs, including potential interactive effects of sedimentation on coral health (Dobbelaere et al, 2020a,b).…”
Section: Introductionmentioning
confidence: 99%
“…It has spread rapidly throughout Florida’s Coral Reef and beyond, resulting in extremely high rates of infection and mortality at affected sites (Precht et al, 2016; Walton et al, 2018; FKNMS, 2018; Alvarez-Filip et al, 2019; Sharp et al, 2020; Dahlgren et al, 2021; Brandt et al, 2021). Localized outbreaks have precipitated significant declines in live coral tissue area (>60%) over short periods of time (Walton et al, 2018; Sharp et al, 2020; Heres et al, 2021; Brandt et al, 2021), with some species being more severely impacted than others (Gintert et al, 2019; Costa et al, 2021; Neely et al, 2021a; Spadafore et al, 2021). In surveys in Miami-Dade county in 2015 and 2016, Precht et al (2016) documented 83% infection in Diploria labyrinthiformis colonies, and estimated that these populations were reduced to <25% of their original numbers.…”
Section: Introductionmentioning
confidence: 99%
“…O ver 20 species of corals along Florida's coral reef have been affected by an ongoing mass mortality event resulting in significant losses of various coral species (1)(2)(3)(4)(5). These mortalities are attributed to a waterborne disease with unknown etiology called stony coral tissue loss disease (SCTLD), which has been continuously spreading since its first observation in 2014 1 .…”
mentioning
confidence: 99%
“…This outbreak of SCTLD represents one of the many "local" threats Florida's coral reefs face that must be mitigated to prevent catastrophic losses driven by global threats like climate change 2 . The SCTLD outbreak has already negatively impacted coral reef ecosystems in Florida 3,4 , so additional local or global threats only further push these reefs past recovery. Unfortunately, by 2018, SCTLD had reached reefs around Mexico 5 , and as of December 2022, at least 26 different Caribbean countries/territories are reporting signs of this disease (https:// www.agrra.org/coral-disease-outbreak/).…”
mentioning
confidence: 99%